Challenges Faced by Teachers About Inculcating Islamic Values: Pilot Inquiry - Muhammad Amin; Tanjeel Ahmed (Indonesian Journal Publisher in cooperation with Indonesian Social Studies Association (APRIPSI), 2021)
This paper examined the different challenges faced by the teachers in inculcating Islamic values among teachers in selected private Islamic secondary schools in the Klang Valley, Malaysia. To achieve the purpose of this study, descriptive analysis (frequencies and percentages) was formulated to direct the study. A survey research design was adopted for the study. The sample of the study consisted of 106 teachers from 145 respondents drawn from the area of the study. The instruments for data collection were first the teachers’ attitudes. Then, the school environment and the last teaching materials/aids. The data were analyzed quantitatively using Statical Package for the Social Sciences (SPSS). The result shows that most teachers, specifically 75%, who participated in this study faced challenges in inculcating Islamic values in teaching at school. The researcher suggested that future research should include additional public school teachers to compare their challenges of inculcating Islamic values.